Stenosis of the Branches of the Neopulmonary Artery after the Arterial Switch Operation: a Cardiac Magnetic Resonance Imaging Study - Thomas, B (2013)
Background : The neonatal arterial switch operation (ASO) is now the standard of care for children born with transposition of the great arteries. Stenosis of the neopulmonary artery on long‑term follow up is a known complication. Methods : We performed a retrospective analysis of eleven patients who underwent a cardiac magnetic resonance imaging (MRI) due to echocardiographic evidence suggestive of stenosis of the neopulmonary artery or its branches (mean estimated Doppler gradient 48 mmHg, min 30 mmHg, max 70 mmHg). A comprehensive evaluation of anatomy and perfusion was done by cardiac MRI. Results : The branches of the neopulmonary artery (neo PA) showed decreased caliber in three patients unilaterally and in two patients, bilaterally. Magnetic resonance (MR) perfusion studies showed concomitant decreased flow, with discrepancy between the two lungs of 35/65% or worse, only in the three patients with unilateral obstruction, by two different MR perfusion methods. Conclusions : Cardiac MR can be used as a comprehensive non‑invasive imaging technique to diagnose stenosis of the branches of the neopulmonary after the ASO, allowing evaluation of anatomy and function of the neoPA, its branches, and the differential perfusion to each lung, thus facilitating clinical decision making.